Effects of Amorphous Calcium Phosphate Administration on Dental Sensitivity during In-Office and At-Home Interventions - Giacomo Oldoini; Antonino Bruno; Anna Maria Genovesi; Luca Parisi (MDPI AG, 2018)
Background. Tooth bleaching is the most frequently employed whitening procedure in clinics. The major side effect of tooth bleaching is dental sensitivity during and after the treatment. Here, we evaluated whether the administration of amorphous calcium phosphate (ACP), during in-office and at-home procedures may impact on dental sensitivity. Methods. Eighty patients, responding to the study requirements were enrolled according to the following criteria. Group 1 (n = 40), received in-office, 10% ACP prior to 30% professional hydrogen peroxide application. The whitening procedure continued at home using 10% carbamide peroxide with 15% ACP for 15 days. Group 2 (n = 40) received only 30% hydrogen peroxide application and continued the whitening procedures at home, using 10% carbamide hydroxide, without ACP- Casein phosphopeptides (CPP), for 15 days. Dental sensitivity was recorded with a visual analogue scale (VAS) at baseline, immediately after, and at 15 days after treatment in the two groups. Results. We observed that patients receiving ACP in the bleaching mixture experienced decreased dental sensitivity (* p ≤ 0.05), as detected by VAS scale analysis immediately following the procedures. Patients receiving ACP-CPP during at-home procedures showed a statistically significant (*** p ≤ 0.0001) reduction of dental sensitivity. Conclusions. We demonstrated that ACP-CPP administration, while exerting the same whitening effects as in control subjects receiving potassium fluoride (PF), had an impact on the reduction of dental sensitivity, improving patient compliance.